2011
DOI: 10.1590/s1413-35552011000200012
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative chest physical therapy prevents respiratory complications in patients undergoing esophagectomy

Abstract: Background: Esophagectomy presents the highest rate of postoperative pulmonary complications among all types of upper abdominal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…This finding was agreed byLunardi et.al, (2010) (76) who concluded that postoperative inspiratory muscle training reduced the rate of respiratory complications, thoracic drainage time, the need to return to mechanical ventilation and the need for chest tube re-insertion.…”
Section: Effect Of Inspiratory Muscle Training Onsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding was agreed byLunardi et.al, (2010) (76) who concluded that postoperative inspiratory muscle training reduced the rate of respiratory complications, thoracic drainage time, the need to return to mechanical ventilation and the need for chest tube re-insertion.…”
Section: Effect Of Inspiratory Muscle Training Onsupporting
confidence: 83%
“…The finding of the current study was in handwithLunardi et.al, (2010) (76) who stated that re-intubation for respiratory failure was lower in the study group than in control group. In contrast, the findings of the current study were contradicted by Elkins et.al, (2105) (70) who found that no statistical significant difference found between the two groups in relation to the need for re-intubation.…”
Section: Effect Of Inspiratory Muscle Training Onsupporting
confidence: 82%
“…Despite this, there are limited studies which look for a direct association between the use of physiotherapy and the prevention of respiratory complications following esophagectomy. One retrospective study did identified lower rates of respiratory complications in those patients receiving postoperative physiotherapy …”
Section: Approaches To Reducing Pulmonary Morbidity After Esophagectomymentioning
confidence: 99%
“…Lunardi et al found that PPC after oesophagectomy are reduced in patients who had undergone chest PT before surgery. Nevertheless the hospital length of stay did not differ in patients treated with PT compared to control patients [42]. Several reviews evaluated the potential effects of chest PT in the pre- and post-operative time.…”
Section: Abdominal Surgerymentioning
confidence: 99%